2019
DOI: 10.1038/s41467-019-12749-7
|View full text |Cite
|
Sign up to set email alerts
|

Spin transport in insulators without exchange stiffness

Abstract: The discovery of new materials that efficiently transmit spin currents has been important for spintronics and material science. The electric insulator Gd3Ga5O12 (GGG), a standard substrate for growing magnetic films, can be a spin current generator, but has never been considered as a superior conduit for spin currents. Here we report spin current propagation in paramagnetic GGG over several microns. Surprisingly, spin transport persists up to temperatures of 100 K Tg = 180 mK, the magnetic glass-like transiti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
58
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 32 publications
(40 reference statements)
3
58
2
1
Order By: Relevance
“…with σ m as the magnon spin conductivity and S S the spin Seebeck coefficient. Thermal magnons can typically diffuse over several μm [36][37][38], which implies that the SSE mainly probes bulk rather than interface magnetic properties. The magnons in simple AFMs typically come in degenerate pairs with opposite polarization that split under an applied magnetic field [11,39].…”
Section: B Spin Seebeck Effectmentioning
confidence: 99%
See 2 more Smart Citations
“…with σ m as the magnon spin conductivity and S S the spin Seebeck coefficient. Thermal magnons can typically diffuse over several μm [36][37][38], which implies that the SSE mainly probes bulk rather than interface magnetic properties. The magnons in simple AFMs typically come in degenerate pairs with opposite polarization that split under an applied magnetic field [11,39].…”
Section: B Spin Seebeck Effectmentioning
confidence: 99%
“…The associated imbalance of the magnon populations cause a nonzero spin Seebeck effect [13]. Paramagnets display a field-induced SSE effect [38] for the same reason, so aligned Dy 3+ moments can contribute to an SSE in DFO.…”
Section: B Spin Seebeck Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…Дальнейшее развитие магнонной спинтроники стимулирует поиск новых механизмов транспорта спинового момента [1]. В частности исследуются возможности переноса спина когерентными фононами в композитных структурах, состоящих из ферромагнитных и акустических слоев [2,3]. Такие структуры получили название магнитоакустические метаматериалы [4].…”
Section: Introductionunclassified
“…There have been several reports of a large SMR or MMR in heterostructures of a HM and a disordered or paramagnetic magnetic insulator. [22][23][24][25][26] However, other experiments showed that in the absence magnetic ordering no MMR can be observed. 27,28 From the theory side, microscopic models to describe the temperature dependence of the SMR have been put forward and good agreement with experiments was found for different material systems.…”
Section: Introductionmentioning
confidence: 99%